Cywilne środki ochrony dobrego imienia Rzeczypospolitej Polskiej na gruncie nowelizacji ustawy o IPN - Kluza, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
On 28 January 2018 the polish parliament passed an act whose task is to take care of the good name of Poland and to fight with the deception of history. To achieve these points, the act introduces appropriate measures of a civil nature. The article presents an overview of civil protection measures for the image of Poland and includes their assessment from the point of view of their feasibility.
Keywords: personal rights; Institute of National Remembrance; deception of history